Identifikasi Tumbuhan Berbiji (Spermatophyta) di Taman Botani Sukorambi Kabupaten Jember untuk Menunjang Mata Kuliah Taksonomi Tumbuhan - Azisah, Fita Elisia; Sudiarti, Diah; Hasbiyati, Haning (JURNAL BIOSHELL, 2021)
Sukorambi Botanical Garden is a natural tourist spot for flora and fauna with a land area of ​​about 12 hectares. In this location, there are about 500 types of plants ranging from lower-grade plants to higher-grade plants. The existence of seed plants (Spermatophyta) of habitus tree in the Botanical Garden has been identified, but there are some plants whose species are not yet known. This research is a descriptive study with a qualitative approach. The method used in this research is a survey method. The research data were analyzed descriptively and identified to the genus level. The results showed that there were 66 genera of seed plants (Spermatophyta) belonging to 30 families. These families are Achariaceae, Anarcadiacea, Annonaceae, Apocynaceae, Araucariaceae, Arecaceae, Bignoniaceae, Burseraceae, Clusiaceae, Ebenaceae, Fabaceae, Gnetaceae, Lamiaceae, Lauraceae, Lythraceae, Malvaceae, Meliaceae, Mimosaceae, Moraceae, Moringaceae, Myristicaceae, Oxalidaceae, Rutaceae, Sapindaceae, Sapotaceae, and Thymelaeaceae. The results of identification can be used as a learning resource to support the Plant Taxonomy course.